CHILDHOOD TRAUMA AND PSYCHOLOGICAL WELL-BEING OF AN ADULT - Hoshovskyi, Jaroslav (Personality and environmental issues, 2025)
The article presents an analysis of modern views on the specifics of childhood trauma and the psychological well-being of an adult. The growing number of socio-political challenges caused by war, economic crisis, etc. does not exclude the presence of complex life experiences that require excessive efforts to maintain and preserve the psychological stability of adults. Unfortunately, traumatic situations can occur in a person’s life regardless of age, including in childhood. This experience often determines the further ontogenesis and prospects of psychological well-being, which determined the interest in this issue. The purpose of the study is to analyze scientific approaches to understanding childhood trauma and the prerequisites for the psychological well-being of an adult. The article applies methods of theoretical study of scientific literature (analysis, synthesis, generalization, comparison of approaches of scientists) in relation to highlighting the problem of childhood trauma and the psychological well-being of an adult. The theoretical methods used present the essence of the concept of childhood trauma and the representation of remote long-term consequences of psychological well-being in adulthood. As a result of the conducted scientific investigations, it was determined that childhood trauma is defined by complex negative events in the ontogenesis of a child, such as emotional, physical, sexual violence, emotional deprivation. It is emphasized that childhood trauma has a deep and long-term impact on the psychological well-being of an adult. It is highlighted that childhood trauma provokes the risk of forming personality pathology, emotional regulation disorders, psychosomatic symptoms, anxiety and depressive disorders. It is presented that the consequences of trauma affect the level of self-esteem, the quality of interpersonal relationships, provoke avoidance of help, and form negative attitudes about oneself and the world. Within the framework of adult life, this is manifested in a tendency to destructive forms of behavior, in particular, substance abuse, a feeling of inner emptiness. Modern scientific views are summarized, which emphasize the importance of supporting self-compassion, positive self-perception and a safe family environment as resources for psychological resilience in adulthood.